Phylogeography and genetic diversity of the microbivalve Kidderia subquadrata, reveals new data from West Antarctic Peninsula - Levicoy, Daniela; Flores, Kamilla; Rosenfeld Sekulovic, Sebastián Alejandro; Cardenas, Leyla (My University, 2021)
It is well established that Antarctic biodiversity has been strongly influenced by rapid climatic fluctuations during the Quaternary. Marine invertebrates from Antarctica constitute an interesting lens through which to study the impacts of the last glacial periods as glaciation impacted the distribution and intraspecific genetic variation of these animals. However, the impact on the spatial genetic distribution and historical demography of local processes in areas adjacent to the West Antarctic Peninsula (WAP) is less clear. Here we present new genetic information on the bivalve Kidderia subquadrata, a small mollusk that inhabits intertidal rocky island ecosystems throughout the WAP. Using a phylogeographical approach, we examined the spatial patterns of genetic diversity in this brooder species to test the hypothesis of strong genetic structure in incubating organisms and the hypothesis of glacial refugia in organisms with limited dispersion. We found evidence of strong genetic structure among populations of the WAP and a recent expansion in the South Shetland Islands. Our findings are concordant with the predictions that incubating organisms, abundant in Antarctica, present a strong genetic structure among their populations and also support the hypothesis of glacial refugia in organisms with limited dispersion. The effect of the coastal current pattern in the WAP is suggested as a driver to the local spatial dynamics of the genetic diversity distribution. Although genetic information about this microbivalve is still scarce, the knowledge reported here has increased our understanding of the evolutionary patterns of this organism that is endemic to the Southern Ocean.
Keywords: Shetland; Peninsula